A review of artificial intelligence strategies in covering array construction - Sughan Nair, Prabhakaran; Adzhar, Kamaludin; Kamal Z., Zamli (AENSI Publishing, 2016)
Software systems are getting larger in size and functionality. Exhaustive software testing is becoming nearly impossible with larger systems. Objective: Researchers are focusing on methods and strategies to optimize software testing process by applying computational based strategies as well as Artificial Intelligence (AI) based strategy. Results: This paper reviews the AI based strategies and its effectiveness in being solution for this optimization problem compared to computational based tools and strategies.